P3‐Type Layered Sodium‐Deficient Nickel–Manganese Oxides: A Flexible Structural Matrix for Reversible Sodium and Lithium Intercalation. Issue 11 (27th July 2015) - Kalapsazova, Maria; Ortiz, Gregorio F.; Tirado, Jose L.; Dolotko, Oleksandr; Zhecheva, Ekaterina; Nihtianova, Diana; Mihaylov, Lyuben; Stoyanova, Radostina
Abstract: Sodium‐deficient nickel–manganese oxides exhibit a layered structure, which is flexible enough to acquire different layer stacking. The effect of layer stacking on the intercalation properties of P 3‐Na x Ni0.5 Mn0.5 O2 ( x =0.50, 0.67) and P 2‐Na2/3 Ni1/3 Mn2/3 O2, for use as cathodes in sodium‐ and lithium‐ion batteries, is examined. For P 3‐Na0.67 Ni0.5 Mn0.5 O2, a large trigonal superstructure with 2√3  a ×2√3  a ×2  c is observed, whereas for P 2‐Na2/3 Ni1/3 Mn2/3 O2 there is a superstructure with reduced lattice parameters. In sodium cells, P 3 and P 2 phases intercalate sodium reversibly at a well‐expressed voltage plateau. Preservation of the P 3‐type structure during sodium intercalation determines improving cycling stability of the P 3 phase within an extended potential range, in comparison with that for the P 2 phase, for which a P 2– O 2 phase transformation has been found. Between 2.0 and 4.0 V, P 3 and P 2 phases display an excellent rate capability. In lithium cells, the P 3 phase intercalates lithium, accompanied by a P 3– O 3 structural transformation. The in situ generated O 3 phase, containing lithium and sodium simultaneously, determines the specific voltage profile of P 3‐Na x Ni0.5 Mn0.5 O2 . The P 2 phase does not display any reversible lithium intercalation. The P 3 phase demonstrates a higher capacity at lower rates in lithium cells, whereas in sodium cells P 3‐Na x Ni0.5 Mn0.5 O2 operates better at higher rates. These findings reveal the unique ability of sodium‐deficient nickel–manganese oxides with a P 3‐type structure for application as low‐cost electrode materials in both sodium‐ and lithium‐ion batteries. Abstract : Squeeze in ! Sodium‐deficient nickel–manganese oxides exhibit a layered structure, which is flexible enough to acquire different layer stacking. Specific features of the P 3‐type structure for reversible and fast sodium and lithium intercalation are demonstrated; this property contributes to the design of low‐cost electrodes for both sodium‐ and lithium‐ion batteries (see figure).